Thinking about the Prophets : A Philosopher Reads the Bible - Seeskin, Kenneth, 1947- (Book collections on Project MUSE., 2020)
"Rethinking the great literary prophets whose ministry ran from the eighth to the sixth centuries BCE- Amos, Hosea, First Isaiah, Jeremiah, Ezekiel, Second Isaiah, and Job-Thinking about the Prophets examines their often-shocking teachings in light of their times, their influence upon later Western and Jewish thinkers, and their enduring lessons for us"--